Transforming growth factor beta 1 (TGFβ1) polymorphisms and unexplained infertility: A genetic association study. (3rd July 2020) - Marhemati, Farnaz; Rezaei, Ramazan; Mohseni Meybodi, Anahita; Taheripanah, Robabeh; Mostafaei, Shayan; Amani, Davar
ABSTRACT: The prevalence of infertility is increasing and worrisome. About 10 to 30% of infertility is classified as idiopathic or unexplained infertility (UI). TGF-β is multifunctional and immunoregulatry cytokine which regulates both implantation and adhesion of trophoblasts to the extracellular matrix during pregnancy. The aim of the current study was to investigate the association between two polymorphisms rs1800470 (C29T) and rs1800471 (G74C) of the TGF-β1 gene in Iranian patients with unexplained infertility. A total of 250 UI patients and 484 healthy individuals with no history of infertility were included in the study. The amplification and sequencing of target DNA fragments were done using PCR and automated sequencing methods, respectively. The effects of these polymorphisms on both TGF-β1 structure and function of mRNA and protein were analyzed using new in-silico tools. The frequency distribution of the alleles, genotypes, and haplotypes of both rs1800470 and rs1800471 polymorphisms had a statistically significant difference between subjects and controls. CC genotype of TGF-β1 rs1800470 (29C→T) increase the risk of UI in male UI patients. Moreover, C alleles of TGF-β1 rs1800471 was associated with increased risk of UI in female UI patients. Couples, subgroup analysis revealed a significant association between TGF-β1 polymorphisms (rs1800470, rs1800471) and the risk of UI in male, female, and all UI patients. The frequency of TG and CG haplotypes were statistically different in both UI and healthy subjects group (P < 0.05). RS1800471 polymorphisms changed the secondary structure of TGF-β1 mRNA and resulted in the removal of one mRNA arm and creation of two new arms. Taken together, the results of the current study suggest that TGF-β1 functional polymorphisms may play an important role in the susceptibility to UI in Iranian population. According to in silico analysis, polymorphisms in TGF-β1 can reduce mRNA half-life and, therefore, reduced TGF-β1 expression.